WAYS TO PROFIT FROM BIG DATA AS A BUSINESS - Sabbagh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Big Data could offer different improvement possibilities for companies and enterprises if they use it with the right toolsto analyze customers purchasing habits in real time. For years, companies have been implementing technologies to optimize their operations. Now in the age of big data, they can capture much more value by gathering information and as much data as possible to gauge customer preferences and needs [1, 2]. As big data analytics dictate, the way enterprises do business; data-driven strategies are becoming an important requirement for competitive differentiation, higher rates of productivity and better profitability. In the following paper, we will look at the ways companies are achieving such a higher level of productivity with the rise of big data. Big data is about exploiting opportunities that were hidden within the historical data [3].It consists of a large volume of structured (zip code, address,)and unstructured data (emails, tweets, Facebook likes) that cannot be processed using traditional IT tools [4]. Analytics and software firms are needed to help companies deal with big data, like Apache Hadoop.